SO2 Gas Physicochemical Removal through Pulse Streamer Discharge Technique Assisted by Vapor Additive. (7th December 2015) - Wang, Xiaojun; Zhang, Lianshui
Abstract : SO2 removal has drawn extensive attentions for air pollution treatment. In this paper, the pulse streamer discharge technique is investigated. Emission spectra diagnosis experimentally indicates that the SO2 molecule has been physically dissociated into SO and O radicals by electron collision and can be remediated through further chemical reactions during and after discharge. In order to quantitatively analyze the removal physical chemistry kinetics, a zero-dimensional physicochemical reaction model is established. Without H2 O vapor additive, the SO2 removal efficiency is leanly low and only 0.296% has been achieved under pulse discharge duration of 0.5 μ s. Through increasing the electrical concentration six times, the removal efficiency has been slightly heightened to 1.796% at pulse duration of 3 μ s. Contrarily, vapor additive can effectively improve the removal kinetics, and removal efficiency has been remarkably heightened to 13.0195% at pulse duration of 0.5 μ s with H2 O/SO2 initial concentration ratio of 0.1 : 1. OH radicals decomposed from H2 O through electron collision are the essential factor to achieve such improvement, which have effectively adjusted the chemical removal process to the favorite directions. The major productions have been transformed from HSO3 and HOSO2 to H2 SO4 when vapor ratio increased above 1.27 : 1.